2018
DOI: 10.1158/0008-5472.can-17-2176
|View full text |Cite
|
Sign up to set email alerts
|

Combined VEGF and PD-L1 Blockade Displays Synergistic Treatment Effects in an Autochthonous Mouse Model of Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) represents the most aggressive pulmonary neoplasm and is often diagnosed at late stage with limited survival, despite combined chemotherapies. We show in an autochthonous mouse model of SCLC that combined anti-VEGF/anti-PD-L1-targeted therapy synergistically improves treatment outcome compared with anti-PD-L1 and anti-VEGF monotherapy. Mice treated with anti-PD-L1 alone relapsed after 3 weeks and were associated with a tumor-associated PD-1/TIM-3 double-positive exhausted T-cell p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
109
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 51 publications
7
109
1
Order By: Relevance
“…5,6 Agents targeting VEGF or VEGFR have demonstrated efficacy in solid tumors, including non-SCLC (NSCLC); 5,6 however, their role in SCLC remains controversial. [7][8][9][10][11] A previous study indicated that the addition of bevacizumab to cisplatin and etoposide in patients with extensive SCLC improved progression-free survival (PFS) and overall survival, 10 but a subsequent report suggested that the addition of bevacizumab to paclitaxel did not improve outcomes in patients with relapsed chemosensitive SCLC. 11 Evidence for the use of anti-angiogenesis drugs for SCLC thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Agents targeting VEGF or VEGFR have demonstrated efficacy in solid tumors, including non-SCLC (NSCLC); 5,6 however, their role in SCLC remains controversial. [7][8][9][10][11] A previous study indicated that the addition of bevacizumab to cisplatin and etoposide in patients with extensive SCLC improved progression-free survival (PFS) and overall survival, 10 but a subsequent report suggested that the addition of bevacizumab to paclitaxel did not improve outcomes in patients with relapsed chemosensitive SCLC. 11 Evidence for the use of anti-angiogenesis drugs for SCLC thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the FGF signaling pathway contributes to resistance to anti-VEGF therapy; however, it is largely unknown how the FGF signaling pathway becomes activated when tumors acquire resistance to anti-VEGF therapy. Recently, the role of the VEGF signaling pathway in cancer immunity has received increased attention because of the promising combination antitumor activity of anti-VEGF therapy with immune checkpoint inhibitors in pre-clinical models 16,17 and clinical trials 18,19 . Therefore, it has become more important to understand the mechanism for acquired resistance to anti-VEGF therapy.Here, we developed novel tumor models for acquired resistance to anti-VEGF therapy by expressing a fusion protein of the mouse VEGFR2 extracellular domain and human IgG4 fragment crystallizable (Fc) region (VEGFR2-Fc) in Renca mouse renal cell carcinoma and B16F10 mouse melanoma cell lines.…”
mentioning
confidence: 99%
“…The study also suggests that miR-210 can serve as a prognostic marker for breast tumors. Together, the interplay between angiogenesis and cancer immune evasion has been investigated in many preclinical studies, which highlight the synergistic effect of immune checkpoint blockade in combination with antiangiogenic agents [111,112]. Conversely, miR-519c, miR-20b, and miR-107 have been reported to suppress vascular endothelial growth factor (VEGF) and HIF-1a expression under hypoxia and thus negatively regulate angiogenesis.…”
Section: The Role Of Mirnas In Modulating Angiogenesismentioning
confidence: 99%
“…2) [110]. Together, the interplay between angiogenesis and cancer immune evasion has been investigated in many preclinical studies, which highlight the synergistic effect of immune checkpoint blockade in combination with antiangiogenic agents [111,112]. Inspired by promising animal studies, many clinical trials are underway to explore the combination of different compounds that target immune checkpoints and angiogenesis (NCT03024437, NCT02659384, NCT02873962, NCT02017717).…”
Section: The Role Of Mirnas In Modulating Angiogenesismentioning
confidence: 99%